Multifunctional polyethylene nanocomposites based on polyethylene-grafted α-zirconium phosphate nanoplatelets. (18th November 2022) - Zhao, Mingzhen; Chen, Hengxi; Zhu, Zewen; Zhu, Xiuzhu; Quan, Yufeng; Zhang, Zhuoran; Wu, Hong-Mao; Wu, Jen-Long; Kang, Wen-Hao; Wang, Qingsheng; Sue, Hung-Jue
Abstract: Multifunctional polymer nanocomposites are gaining significant interest due to the ever-increasing application demands for high performance polymers. In this study, a nanoplatelet functionalization methodology was developed to achieve its well exfoliation and multifunctionality in polyethylene (PE). In addition to the commonly known benefits of the improved modulus and barrier properties, the nanoplatelets can be grafted with fire retarding molecules to further improve flame retardancy of PE. Specifically, PE nanocomposites consisting of well-exfoliated α-zirconium phosphate (ZrP) was prepared via grafting of maleated PE (MPE) on ZrP (ZrP-MPE). The exfoliated ZrP-MPE was further covalently modified with additional phosphorous-based functional group to achieve improved flame retardancy. The grafted MPE on ZrP can co-crystallize with PE matrix to stabilize ZrP exfoliation in PE matrix. The observed synergistic flame retardation effect is attributed to the barrier effect of the well-exfoliated ZrP and gas phase radical trapping by the phosphorous-based functional group on ZrP surface. The usefulness of the present study for preparation of multifunctional polymer nanocomposites is discussed. Graphical abstract: Image 1 Highlights: Developed methodology to prepare multifunctional polymer nanocomposites containing high concentration of well-exfoliated 2D nanoplatelets. Established strong ZrP-g-polyethylene and polyethylene matrix co-crystallization. Improved polyethylene flame retardancy.